Impact of hyperoxic preconditioning in normobaric hypoxia (3500 m) on balance ability in highly skilled skiers: A randomized, crossover study - Morawetz, D.; Dünnwald, T.; Faulhaber, M.; Gatterer, H.; Schobersberger, W. (International Journal of Sports Physiology and Performance, 2019)
It is well known that acute hypoxia has negative effects on balance performance. An attempt to compensate for the influence of hypoxia on competition performance was made by the application of hyperoxic gases (inspiratory fraction of oxygen >0.2095) prior to exercise. Purpose: To investigate whether hyperoxic preconditioning (pure-oxygen supplementation prior to exercise) improves balance ability and postural stability during normobaric hypoxia (3500 m) in highly skilled skiers. Methods: In this single-blind randomized, crossover study, 19 subjects performed a 60-s balance test (MFT S3-Check) in a normobaric hypoxic chamber. After a short period of adaptation to hypoxia (60 min), they received either pure oxygen or chamber air for 5 min prior to a balance test (hyperoxic preconditioning vs nonhyperoxic preconditioning). Capillary blood was collected 3 times. Results: Balance performance, indexed by sensory (P=.097), stability (P=.937), and symmetry (P=.202) scores, was not significantly different after the hyperoxic preconditioning phase. Balance performance decreased over time (no group difference). After hyperoxic preconditioning, arterial partial pressure of oxygen increased from 52.7 (4.5) mm Hg to 212.5 (75.8) mm Hg, and oxygen saturation of hemoglobin increased from 85.8% (3.5%) to 98.9% (0.7%) and remained significantly elevated to 90.1% (2.0%) after the balance test. Conclusion: A hyperoxic preconditioning phase does not affect balance performance under hypoxic environmental conditions. A performance-enhancing effect, at least in terms of coordinative functions, was not supported by this study.